A new silicon-based root canal sealer (Roekoseal((R))-Automix) - TÜRKMEN, CAFER (BLACKWELL PUBLISHING LTD, 2003)
This study evaluated the new silicon-based sealer 'Roekoseal((R)) -Automix' (RSA) with respect to sealing, bonding capabilities and biocompatibility with rat subcutaneous connective tissue. For the microleakage study, 36 single rooted teeth were instrumented and 30 of these obturated with either Grossman's sealer or RSA using lateral condensation technique (15 of each). Six teeth were not obturated and used as control group. For investigating bonding capability, 10 of the obturated roots with RSA and Grossman's sealer were ground and split longitudinally and examined by scanning electron microscopy (SEM). The RSA was found to seal significantly better than Grossman's sealer. The SEM examination revealed a good bond between RSA and the dentine and between RSA and the gutta-percha. Tissue reaction was evaluated by injecting 0.1 mL RSA into the connective tissue of 21 male Albino-Wistar rats and observing at 24 h, 7 days and 30 days and 30 days. Formation of a new granulation tissue with fibrous tissue adjacent to the material at 30 days. This study found that RSA performed well.
Keywords: dye penetration; Roekoseal; root canal sealer; silicon